STUDI LITERATUR PENGARUH RAGAM MODEL PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA PADA MATA PELAJARAN BIOLOGI - Toni Efriyandika; Mujiati; Zulkifli Tambe; Rr Eko Susetyarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is a vehicle for improving and developing the quality of human resources. Apart from that, education is a set of processes in the form of instilling values, ideas, concepts and theories aimed at developing personality, knowledge, skills and behavior as well as achieving ideals and life goals. Achieving learning goals in the form of learning achievement is the result of learning activities. The quality in the classroom is influenced by many complex things that are interrelated with each other, for example learning methods, learning models, learning strategies and so on. The low level of student activity when learning biology occurs because students only receive information conveyed by their teacher. Students don't want to think, students don't want to try to find concepts and solve problems that have been given by their teacher. The aim of this research is to determine the influence of various learning models on students' critical thinking abilities in biology material based on literature studies. So this research is entitled "literature study of the influence of various learning models on students' critical thinking abilities in biology material".